Impact of DASH and mediterranean diets on mood and happiness in young adult males: a cross-sectional study - Shervin Kazeminejad; Mitra Abtahi; Mohammadreza Askari; Motahare Hatami Marbini; Yahya Jalilpiran; Leila Azadbakht (BMC Research Notes)
Abstract Objective The association between the Mediterranean diet (MED) and the dietary approach to stop hypertension (DASH) with some mental disorders is well-documented. However, a consistent relationship with young adults as a vulnerable population has yet to be known. Therefore, we aimed to investigate the relation between Iranian young male adults’ mood and happiness state with DASH/MED patterns. Results Participants’ mean age was 23.65 ± 1.74 years, within the age range of 18–28 years, and their BMI was 24.23 ± 3.82 kg/m². After adjusting for all covariates, those in the highest DASH tertile had 54% lower odds of poor mood compared to the lowest tertile (OR = 0.46; 95%CI: 0.24, 0.88). An inverse relationship was also found between DASH and low happiness scores (OR T3 vs. T1 = 0.51, 95%CI: 0.27, 0.96). No significant association was found between MED and mood or happiness. Therefore, results showed that participants who adhered more closely to the DASH diet were less likely to report being unhappy or having a poor mood. Further prospective studies are required to confirm these findings.